Analisis Kinerja Tenaga Pendorong Reservoir dan Perhitungan Water Influx pada Perolehan Minyak Tahap Primer (Studi Kasus Lapangan Falipu) - Ira Herawati (Journal of Earth Energy Engineering, 2016)
Primary recovery is the stage of oil production by relying on the natural ability of the driving force of the reservoir. Kind of driving force that is water drive reservoir, depletion drive, segregation drive and a combination drive. The pressure drop occurred along its produced oil from the reservoir. Reservoir so that the driving force is the main parameter in maintaining reservoir pressure balance. Through the concept of material balance is the determination of the type of propulsion quifer reservoir and the power that generates driving force parameter analysis capability and aquifer in oil producing naturally. Then do the forecasting production to limit the ability of primary recovery production phase. Combination drive depletion of water drive and the drive is a driving force in the dominant reservoir Falipu Fields with a strongly water aquifer types of drives obtained through material balance equation. Calculations using the method of water influx Havlena & Odeh used as a correction factor for determining the type of propulsion reservoir and aquifer strength. Forecasting production in the Field Falipu generate recovery factor of 41% with a pressure boundary in 2050.